Stres Kerja Lebih Dominan Dari Kebisingan: Analisis Korelasional Terhadap Kelelahan Pekerja Di Industri Penggergajian Kayu - Lina Handayani; Pungki Yulia Fitriani; Tria Nisa Novianti (Universitas Ivet, 2025)
Work fatigue is one of the significant occupational health issues as it can reduce productivity and increase the risk of workplace accidents. This study aims to analyze the relationship between noise intensity and work stress on work fatigue among workers in the wood sawmill industry. This quantitative study with a correlational design was conducted at UD Jati Widodo, Pati Regency, involving 38 respondents selected through total sampling. Noise levels were measured using a Sound Level Meter, work stress was assessed using a validated and reliable questionnaire, and work fatigue was measured using a Reaction Timer based on light stimulus. Analysis using the Spearman test showed a significant and positive correlation between work stress and work fatigue (p = 0.004; r = 0.462), while the relationship between noise and work fatigue was also significant but with a negative correlation (p = 0.016; r = -0.388). These findings indicate that work stress is a more dominant factor influencing fatigue than noise. Practically, the results of this study recommend the importance of work stress management as a preventive measure to reduce work fatigue among workers in the wood sawmill industry, such as through psychosocial counseling, job rotation, or stress coping training.